Deletion and duplication sequences induced in CHO cells by teniposide (VM-26), a topoisomerase II targeting drug, can be explained by the processing of DNA nicks produced by the drug-topoisomerase interaction - Ripley, Lynn S. (Mutation Research, 1994)
Frameshift mutations induced by acridines in bacteriophage T4 have been shown to be due to the ability of these mutagens to cause DNA cleavage by the type II topoisomerase of T4 and the subsequent processing of the 3′ ends at DNA nicks by DNA polymerase or its associated 3′ exonuclease followed by ligation of the processed end to the original 5′ end. An analysis of the ability of nick-processing models is presented here to test the ability of nick processing to account for the DNA sequences of duplications and deletions induced in the aprt gene of CHO cells by teniposide (VM-26) [Han et al. (1993) J. Mol. Biol., 229, 52]. Although teniposide is not an acridine, it induces topoisomerase II-mediated DNA cutting in aprt sequences in vitro and mutagenesis in vivo. Although the previous study noted a correlation between mutation sites and nearby DNA discontinuities induced by the enzyme in vitro, neither the nick-processing model responsible for T4 mutations, nor double-strand break models alone were able to account for most of the mutant sequences. Thus, no single model explained the correlation between teniposide-induced DNA cleavage and mutagenic specificity. This report describes an expanded analysis of the ways that nick-processing models might be related to mutagenesis and demonstrates that a modified nick-processing model provides a biochemical rationale for the mutant speficities. The successful nick-processing model proposes that either 3′ ends at nicks are elongated by DNA polymerase and/or that 5′ ends of nicks are subject to nuclease activity; 3′-nuclease activity is not implicated. The mutagenesis model for nick-processing of teniposide-induced nicks in CHO cells when compared to the mechanism of nick-processing in bacteriophage T4 at acridine-induced nicks provides a framework for considering whether the differences may be due to cell-specific modes of DNA processing and/or due to the precise characteristics of topoisomerase-DNA intermediates created by teniposide or acridine that lead to mutagenesis.